Electrochemical properties of the soluble reduction products in rechargeable Li/S battery - Li, Yajuan; Zhan, Hui; Liu, Suqin; Huang, Kelong; Zhou, Yunhong (Journal of power sources, 2010)
In this paper, the electrochemical behavior of the reduction products in solution for Li/S cell is studied by UV–visual spectroscopy and electrochemical impedance spectroscopy (EIS). The results tell that the redox process of the polysulfide intermediate contains five charge-transfer steps in the practical Li/S cell. The formation of final reduction product of Li 2S and the final re-oxidation product of S 8 is completely irreversible. The transform between polysulfide and Li 2S 2 is electrochemical sluggish. The peaks corresponding to transformation Li 2S x ↔ Li 2S y (2 < x < y ≤ 6) are still symmetrical in spite of an increasing polarization with the proceeding of CV scan. While the redox process corresponding to Li 2S m ↔ Li 2S n (4 < m < n ≤ 8) is reversible. The dissolution long-chain polysulfide and deposition of short-chain polysulfide contribute mostly to the electrode deterioration even electrode blockage. Therefore, homogeneous mixing element sulfur with conductive components and alleviating the polysulfide dissolution are equally important to improving the active material utilization and rechargeability for rechargeable Li/S battery.